Pemanfaatan modalitas dalam pidato inspiratif: analisis retorika pidato Maudy Ayunda sebagai JUBIR G20 - Afrisyah, Misbahul; Kurniawan, Bima (CV. Kurnia Grup, 2024)
This study examines Maudy Ayunda's speech as a spokesperson at the G20 Presidency event from December 1, 2021, to November 30, 2022, with the theme